Pengurusan disiplin murid di sekolah kawasan bandar dan luar bandar: perspektif pemimpin sekolah - A. Ghani, Muhammad Faizal; Mohd Radzi, Norfariza; Ghavifekr, Simin; Kenayathulla, Husaina Banu; Muhamad, Mohd Mokhtar (Faculty of Education, University of Malaya, 2014)
Although the low achievement of a school discipline associated with students’ misconduct, there is a high correlation between good school discipline and student achievement. Therefore, this study aims to identify the effectiveness and differences of school discipline management in urban and rural areas. A quantitative survey method was applied and questionnaire was distributed to the total of 80 school leaders that included 47 from urban and 33 from rural areas in selected schools in Malaysia. Data were analyzed using descriptive statistic including percentage, mean, and standard deviation, and inferential statistic for Mann-Whitney U test. The study found that the effectiveness of managing students’ discipline in both rural and urban schools is high and shows satisfactory when the mean score is 4.00 and standard deviations is 0.79. Furthermore, the results show that that there is no significant differences between urban and rural schools in managing the students’ discipline at p>0.05. In addition, this study found that the importance of the school factors especially school leaders in managing the students’ discipline systematically involving planning, organizing, leading and controlling.